1997
DOI: 10.1046/j.1365-3083.1997.d01-116.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses in Mice After Gastric and Subcutaneous Immunization with BCG

Abstract: Ibsen MW, Bakken V, Jonsson R, Hordnes K. Immune Responses in Mice After Gastric and Subcutaneous Immunization with BCG. Scand J Immunol 1997:46:274-280 Mucosal immunization can induce immune responses different from those induced by systemic immunization. In this study, murine immune responses were analysed after immunization through gastric and subcutaneous routes with Mycobacterium bovis BCG. The number of circulating cells secreting antigenspecific immunoglobulins (Ig), and the number of gamma interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In our initial studies we wished to establish the character of the immune response induced by BCG via the intravesical route. Previous studies have shown that immunization by different routes generate diverse effector responses [27,40]. Moreover, it is known that mycobacteria can induce both Th1 and Th2 responses[16,41].…”
Section: Discussionmentioning
confidence: 99%
“…In our initial studies we wished to establish the character of the immune response induced by BCG via the intravesical route. Previous studies have shown that immunization by different routes generate diverse effector responses [27,40]. Moreover, it is known that mycobacteria can induce both Th1 and Th2 responses[16,41].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of literature exists documenting immune responses to systemic challenge with mycobacteria in murine models [6–8]. However, it has been demonstrated that immune responses to systemic and lung infections with mycobacteria are substantially different.…”
Section: Introductionmentioning
confidence: 99%